Swept volume dinamical systems and their kinetic models - Bogoliubov, N.N.; Prykarpatsky, A.K.; Blackmore, D. (Нелінійні коливання, 1999)
We study swept-volume dynamical systems for which several hydrodynamical models are formulated. The properties of those hydrodynamical models are studied by means of the algebraic Kostant – Symes technique. A differential-geometric description of swept volumes dynamical systems are devised based on the Cartan Movina frame approach. Для динамiчних систем, породжених орбiтами точок деякої частини фазового простору, наведено декiлька гiдродинамiчних моделей, властивостi яких дослiджуються за допомогою методу Костанта – Сiмза. В рамках пiдходу Картана дано диференцiально-геометричний опис вказаних систем.